Characteristics of a lipase ArEstA with lytic activity against drug-resistant pathogen from a novel myxobacterium, Archangium lipolyticum sp. nov. - Zhou, Yang; Chen, Haixin; Jiang, Hongxia; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2024)
Bacteriolytic myxobacteria are versatile micropredators and are proposed as potential biocontrol agents against diverse bacterial and fungal pathogens. Isolation of new myxobacteria species and exploration of effective predatory products are necessary for successful biocontrol of pathogens. In this study, a myxobacterium strain CY-1 was isolated from a soil sample of a pig farm using the Escherichia coli baiting method. Based on the morphological observation, physiological test, 16S rRNA gene sequence, and genomic data, strain CY-1 was identified as a novel species of the myxobacterial genus Archangium, for which the name Archangium lipolyticum sp. nov. was proposed. Subsequent predation tests indicated that the strain efficiently lysed drug-resistant pathogens, with a higher predatory activity against E. coli 64 than Staphylococcus aureus GDMCC 1.771 (MRSA). The lysis of extracellular proteins against ester-bond-containing substrates (tributyrin, tween 80, egg-yolk, and autoclaved drug-resistant pathogens) inspired the mining of secreted predatory products with lipolytic activity. Furthermore, a lipase ArEstA was identified from the genome of CY-1, and the heterologously expressed and purified enzyme showed bacteriolytic activity against Gram-negative bacteria E. coli 64 but not against Gram-positive MRSA, possibly due to different accessibility of enzyme to lipid substrates in different preys. Our research not only provided a novel myxobacterium species and a candidate enzyme for the development of new biocontrol agents but also reported an experimental basis for further study on different mechanisms of secreted predatory products in myxobacterial killing and degrading of Gram-negative and Gram-positive preys.